Effect of Period and Storage Conditions on Essential Oil Yield And Composition of Eucalyptus Citriodora Leaves - Mu’azu, K.; Ganiyu, A.; Alkali, A. S.; Ahmed, A. U.; Jibia, S. M.; Shehu, M.; Adamu, I. U. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Fresh eucalyptus citriodora leaves were harvested and kept under shade and sun for a period of four weeks. The effect of storage conditions and period of storage on the oil yield, oil composition and extraction pattern of the oil were investigated. It was observed that for the leave kept under sun there was significant decrease in the oil yield from 0.38% in the 1st week to 0.11% in the 4th week. However, for leaves kept under shade the oil yield slightly decreased from about 0.40% in the 1st week to 0.36% in the 4th week. The results further revealed that the storage condition and period of storage had no effect on the extraction pattern of the oil with about 72% of the oil extracted within 40 minutes of extraction time after induction period of 24 minutes. Two mathematical model equations were developed for the prediction of oil yield as a function of storage time for both conditions. The models predicted that for leaves stored in the shade and sun the expected oil yield would be 34.5% and 1% respectively. Physiochemical analysis of the oils revealed that the properties of the oil were not affected by both the period and condition of storage except the colour which changed from pale yellow to light brown. These results imply that the leaves should best be kept under shade before production in order to preserve its oil content and physiochemical properties.